Stalking-some general questions and comparative law overview - Kovačević Milica (Strani pravni život, 2018)
Interest for the phenomenom of stalking has been on the rise over recent years, especially because it can sometimes be turned into serious crimes. This is why an increasing number of countries are opting for the introduction of new incriminations that will include stalking. However, the incrimination of persecution opens the problem of distinguishing this criminal offense from other related criminal offenses, and the question arises as to how the offense should be defined so that there is no excessive limitation of other rights and freedoms of citizens. Therefore, the paper is focused on general considerations concerning stalking and on the analysis of comparative solutions. Given that in Serbia stalking has been incriminated only recently, the aim of the paper is to point out to some of the problems that can be expected in practice, and to extricate some possible solutions.